THE ROLE OF GUT MICROBIOTA IN ADOLESCENT MENTAL HEALTH: A SYSTEMATIC REVIEW - Abdullah, Dessy; Vika Sarmila Fitri (Nusantara Hasana Journal, 2025)
Mental health issues such as anxiety and depression are increasingly prevalent among adolescents. The gut–brain axis has been highlighted as a key pathway through which the gut microbiota may influence mood, behavior, and emotional regulation. To systematically review current scientific literature on the relationship between gut microbiota and adolescent mental health, as well as the potential of dietary interventions. A systematic literature search was conducted using PubMed, Scopus, and Google Scholar with keywords including “gut–brain axis,” “microbiota,” “mental health,” “adolescent,” and “nutrition.” Eligible studies were original articles or systematic reviews published in the past ten years, in English, and focused on individuals aged 10–24. A total of 28 articles met the inclusion criteria. Most studies found significant links between gut microbiota composition and psychiatric symptoms such as anxiety and depression. Interventions using probiotics, prebiotics, and traditional fermented foods showed potential in reducing stress and improving emotional well-being. Gut microbiota plays a crucial role in regulating adolescent mental health. Dietary interventions using locally available fermented foods such as tempeh and dadiah may serve as effective preventive strategies.